ANALYZING THE HANDLING OF THE COVID-19 PANDEMIC IN DKI JAKARTA: WAS IT SUCCESSFUL OR FAILED? - Diraisnu Gozali; Muhammad Yaumal Yusril (Departemen Administrasi Publik, Universitas Diponegoro, 2022)
The purpose of this research is to determine how effectively the DKI Jakarta Province's COVID-19 pandemic management plans have been implemented. Although the government of DKI Jakarta Province has implemented a number of strategies to combat the COVID-19 pandemic, they are unable to halt the virus's spread. This study employs literature research techniques. This research intends to incorporate pertinent literature and data in order to produce a comprehensive article; consequently, literature research is utilized in this article. This study shows that the efforts and policies of the DKI Jakarta Province government have not stopped the spread of COVID-19 in DKI Jakarta Province. Policies and handling efforts are still being thwarted by large-scale social restrictions imposed by the government, community dissatisfaction with health standards, and ineffective coordination between the federal and local governments.